REPRODUCTIVE POTENTIAL OF SECOND LACTATION DAUGHTERS FROM HOLSTEIN MOTHER COWS OF DIFFERENT AGES - Kapshuk, N. O. (Scientific Progress & Innovations, 2020)
The article highlights the research results of the level of reproductive function indices of the second lactation Holstein cows, born to mothers of different ages. The studies were performed on the second lactation animals, which included: cows born from mother cows in the first lactation (n=22) - group I; cows born from mother cows in the second lactation (n=25) – group II; cows born from mother cows in the third lactation (n=28) – group III (control); cows born from cows in the fourth lactation (n=23) – group IV. Animals of all experimental groups had unmatched value of the service period. Cows of the second lactation (group I), which were born from first-calf heifers, had the lowest value of the recovery period after calving – 1.0. In cows of the III (control) group, which were born by mothers of the third lactation, the service period already lasted more than 80 days, while in cows of the second lactation in group IV, which were born by mothers of the fourth lactation, this figure was 5 times higher and amounted to almost 5. The value of insemination index is directly proportional to the service period indicator. Its value in cows of group I corresponded to the classical reproduction scheme, and made almost no more than 60 days, while in animals of the same age of group IV, the service period was more than 4 times longer and made 222 days. Infertility level of daughter cows in the second lactation can be explained by the fact how effectively their reproductive system functions. Animals in group I did not have infertile days and milk and calf losses. In animals of groups II and III (control), the level of infertility was 13.3 and 20.3 days, respectively, which resulted in calves and milk losses of 0.045 heads and 308.4 kg, on average. Cows of group IV were distinguished by the highest infertility value – 151 days and product losses – 0.53 heads of calves and 2,597 kg of milk. The experimental herd of cows of groups I, II and III (control) was characterized by a positive value of adaptation index, which averaged 1.21. In contrast, cows in group IV had a negative value of adaptation index (-6.3), which exceeded the value of this indicator of cows in group III (control) by more than 26 times, and animals in group I by 32 times.